Maxillofacial Fractures in CT scan Images of Adult, Adolescent, and Child Patients in Radiology Ward of Mashhad’s Shahid Kamyab Emergency Hospital in 2010 - Najmeh Anbiaee; Touraj Vaezi; Farshad Khamchin; Fatemeh Hafez Maleki (Journal of Dental Materials and Techniques, 2015)
Introduction: This study was conducted to determine the pattern of maxillofacial fractures in three age groups of adults, adolescents, and children, using CT scan images. Methods: In this cross-sectional study, CT scan images of 230 patients with maxillofacial trauma during one year were examined in terms of the number and site of fractures. The patients were divided into three age groups, children (0-14 years), adolescents (14-17 years), and adults (>17 years). The data collected from this group were analyzed using, Chi-square, independent t-test and ANOVA statistical tests. Results: The analysis showed that 85% of maxillofacial fractures occur in adults, 7% in adolescents, and 8% in children. The most prevalent causes of fractures in adults were accidents (70%) and fallings (16%). Accidents (73%) and quarrels (13%) were the most prevalent causes of fractures in adolescents. In children, falling (60%) as the most prevalent cause of fracture was significantly higher than that in other groups (P-value=0.001). The most prevalent sites of maxillofacial fracture in adults were nasal bones and zygomaticomaxillary complex. Nasal and orbital fractures in adolescents comprised the most prevalent sites of fracture. Mandibular bone was the most prevalent site of fracture in children. The variations in prevalent sites of fracture among the three groups were significant (P-value=0.002). Conclusion: Car accidents are the main risk factor for maxillofacial fractures. The prevalent causes and sites of maxillofacial fractures in adults, adolescents, and children are different from one another.